The Norton history of technology (W.W. Norton, 1995)
The latest volume in Norton's "History of Science" series is as sweeping in scope as its predecessors (John North's Norton History of Astronomy and Cosmology, LJ 7/94). Cardwell, distinguished historian at the University of Manchester, divides his synthesis into three broad chronological periods: the ancients, the Industrial Revolution, and the modern era. Throughout, he emphasizes the importance to technical development of contemporary thinking about knowledge and progress, pointing out that a true understanding of the history of technology demands some familiarity with the thought of Aristotle, Bacon, Aquinas, et al. This work is not the easiest reading at times, but as a rare (and probably the best) single-volume treatment of an almost overwhelming subject usually covered in multi-volume sets, it deserves a place in all academic and public science collections.